Evaluation of two vaccines for the treatment of pythiosis insidiosi in horses - Mendoza, Leonel (1992)
Two vaccines to treat pythiosis insidiosi in horses were evaluated in 71 Costa Rican horses between 1982 to 1988. One vaccine used a cell-mass (CMV) as antigen and the other a soluble concentrated antigen (SCAV). Both vaccines cured horses infected with Pythium insidiosum (p value- 14%). The age of lesions prior to vaccination was important in the response of the horses to immunotherapy. All horses with lesions 0.5 months or less in duration were cured regardless of the vaccine used. Horses with lesions two or more months old did not respond to either vaccine. The age of the horses did not have any influence on their response to the vaccinations. The CMV produced a prominent inflammatory reaction at the side of injection, while the SCAV gave a low inflammatory reaction. In addition, the CMV lost its effectiveness two to three weeks after its preparation. By contrast, the SCAV maintained its ability to cure horses even after 18 months. Immunotherapy using SCAV can thus be used as the vaccine of choice in early cases of equine cutaneous pythiosis insidiosi.